PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN TRIBUNNEWSBOGOR.COM - Iin Asikin; Kanaria Kanaria; Indra Suyahya (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Job satisfaction gets serious attention from various parties, someone who has a high level of satisfaction has positive feelings about his job, while someone with a low level has negative feelings about his job. On the other hand, someone who is dissatisfied, does not perform well and will become an obstacle to the success of the organization. For this reason, companies need to pay attention to several factors that affect employee job satisfaction, namely transformational leadership and work environment. This study aims to find out empirically and provide input and contribution to increasing employee job satisfaction through the application of transformational leadership and the creation of a conducive work environment.